2000
DOI: 10.1023/a:1004163315822
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The human oviduct epithelium primarily consists of ciliated cells and secretory cells. Solitary cilia usually extend from the apical surface of the secretory cells. We investigated the localization of gamma-tubulin in the ciliary basal apparatus of both cell types by fluorescence immunohistochemistry and immunoelectron microscopy. In addition to basal bodies, gamma-tubulin was identified in the lateral basal foot, especially the basal foot cap. This observation is consistent with previous observations that mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Galectin-3 was detected at the ciliary rootlet and at the basal foot cap (Figure 3C, black arrows and black arrowheads, respectively). Basal foot caps and ciliary rootlets have been suggested to be the MT anchoring sites of the BB, and are now considered as the MT organizing centers (MTOCs) of the cilium base 26, 27, 28. Consistently, immunogold staining revealed that γ-tubulin is located at the basal foot cap and at the ciliary rootlet in mouse tracheal multiciliated cells (Figure 3D, arrows and arrowheads, respectively), as previously observed in oviduct epithelial cells 27.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Galectin-3 was detected at the ciliary rootlet and at the basal foot cap (Figure 3C, black arrows and black arrowheads, respectively). Basal foot caps and ciliary rootlets have been suggested to be the MT anchoring sites of the BB, and are now considered as the MT organizing centers (MTOCs) of the cilium base 26, 27, 28. Consistently, immunogold staining revealed that γ-tubulin is located at the basal foot cap and at the ciliary rootlet in mouse tracheal multiciliated cells (Figure 3D, arrows and arrowheads, respectively), as previously observed in oviduct epithelial cells 27.…”
Section: Resultssupporting
confidence: 79%
“…Basal foot caps and ciliary rootlets have been suggested to be the MT anchoring sites of the BB, and are now considered as the MT organizing centers (MTOCs) of the cilium base 26, 27, 28. Consistently, immunogold staining revealed that γ-tubulin is located at the basal foot cap and at the ciliary rootlet in mouse tracheal multiciliated cells (Figure 3D, arrows and arrowheads, respectively), as previously observed in oviduct epithelial cells 27. Given Galectin-3 localization with the basal foot cap, we conclude that this lectin is associated with the cilium base MTOC.…”
Section: Resultsmentioning
confidence: 99%
“…Either antibodies against known markers of the basal body and the basal foot or lentivirally expressed epitope-tagged transgenes can be used with the various super-resolution microscopy techniques. Here, we will focus on three-dimensional structured illumination microscopy (3D-SIM) immunofluorescence imaging of the transition fiber component Cep164 (Graser et al, 2007; Lau, Lee, Sahl, Stearns, & Moerner, 2012) and the basal foot component γ-tubulin (Hagiwara, Kano, Aoki, Ohwada, & Takata, 2000) (Figure 3). 3D-SIM requires minimal adjustment to established immunofluorescence protocols, while permitting super-resolution imaging in up to four channels.…”
Section: Assessment Of Ultrastructural Planar Polarity Of Motile Cmentioning
confidence: 99%
“…Almost all cell types have a monocilium, a microtubule-based structure protruding into the extracellular space [49]. In the case of an epithelial cell, the primary cilium is localized in the apical surface.…”
Section: Function At the Primary Ciliummentioning
confidence: 99%
“…In the case of an epithelial cell, the primary cilium is localized in the apical surface. The cilium is formed from the basal body in growth arrested cells [49]. While the exact function of the immotile, primary cilium of kidney epithelial cells is not well understood, it is now well established that loss of ciliary function and/or formation results in cystic diseases pointing to a central role of this organelle in PKD pathophysiology [50,51].…”
Section: Function At the Primary Ciliummentioning
confidence: 99%